2022
DOI: 10.1155/2022/1019289
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Multitarget Mechanism and Active Compounds of Essential Oil from Artemisia argyi Treating Pressure Injuries Based on Network Pharmacology

Abstract: In order to comprehensively explore multitarget mechanism and key active compounds of Artemisia argyi essential oil (AAEO) in the treatment of pressure injuries (PIs), we analyzed the biological functions and pathways involved in the intersection targets of AAEO and PIs based on network pharmacology, and the affinity of AAEO active compounds and core targets was verified by molecular docking finally. In our study, we first screened 54 effective components according to the relative content and biological activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…These days, multicomponent drugs that hit multiple targets are attracting attention. Moreover, whole extract from a single natural product and compound prescription contain various ingredients, thus multi-target cancer treatment is possible ( Chang et al, 2020 ; Lu et al, 2022 ). Therefore, it is necessary to pay more attention to cancer treatment using natural products.…”
Section: Discussionmentioning
confidence: 99%
“…These days, multicomponent drugs that hit multiple targets are attracting attention. Moreover, whole extract from a single natural product and compound prescription contain various ingredients, thus multi-target cancer treatment is possible ( Chang et al, 2020 ; Lu et al, 2022 ). Therefore, it is necessary to pay more attention to cancer treatment using natural products.…”
Section: Discussionmentioning
confidence: 99%
“…95 The results revealed that the top seven active compounds of Artemisia argyi essential oil had good affinity for key targets, and that the root mean square deviation of each docking target and compound was <2 angstroms. 95 In summary, the application of network pharmacology and molecular docking technology can effectively clarify the pharmacodynamic material basis of complex chemical substance systems, and improve the efficiency in drug discovery and development via the EO screening process. 71,96…”
Section: Application Of Network Pharmacology In Essential Oil Researchesmentioning
confidence: 98%